The Combination of Sonographic Features and the Seven-Gene Panel May be Useful in the Management of Thyroid Nodules With Indeterminate Cytology - Capezzone, Marco; Cantara, Silvia; Di Santo, Andrea; Sagnella, Alfonso; Pilli, Tania; Brilli, Lucia; Ciuoli, Cristina; Maino, Fabio; Forleo, Raffaella; Cartocci, Alessandra; Castagna, Maria Grazia (Frontiers in Endocrinology, 2021)
Introduction. The management of patients with indeterminate thyroid nodules, which account for 10–25% of thyroid fine needle aspiration biopsies (FNABs), is still very challenging. Aim. To verify the utility of the 7–gene panel in combination with ultrasound features, in the clinical management of indeterminate thyroid nodules. Results: The study group included 188 indeterminate thyroid nodules, divided into TIR3A (56.4%) and TIR3B (43.6%). A significant correlation between US categories and both cytological and molecular results was observed. In detail, TIR3B cytology was more frequent in EU-TIRADS 4 and 5 nodules (54.7% and 50%, respectively) than in EU-TIRADS 2 and 3 nodules (31%, p=0.04). Similarly, the rate of a nodule with a mutation increased with the increase of US risk class (6.0% in EU-TIRADS 2 and 3, 9.3% in EUTIRADS-4 and 27.8% in EUTIRAD-5, p=0.01). Among thyroid nodules submitted to surgery, final histology was benign in 61.4% nodules while malignancy was diagnosed in 38.6% nodules. Using US score as tool for decision-making in TIR3A subgroup, we correctly classified 64.5% of thyroid nodules. The second tool (7-gene panel test) was used in the subgroup of US high-risk nodules. By multiple tests with series approach (US in all cases and US plus 7-gene panel in US high risk nodules) 84% of cases were correctly classified. In TIR3B nodules, using only 7-gene panel as tool for decision making, we correctly classified 61.9% of indeterminate nodules. By multiple tests with series approach (7-gene panel in all cases and 7-gene panel plus US score in non-mutated nodules) only a slight improvement of thyroid nodule classification (66.6%) was observed. Conclusions: US score seems able to correctly discriminate between TIR3A nodules in which a conservative approach may be used, and those in which additional test, such as molecular test, may be indicated. On the contrary, in TIR3B nodules both US risk stratification and 7-gene panel, seem to be of little use, because the risk of thyroid cancer remains high regardless US score and mutational status.